2017
DOI: 10.1177/2165079917734880
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc Supplementation on Sleep Quality of ICU Nurses: A Double Blinded Randomized Controlled Trial

Abstract: This study examined the effect of zinc supplementation on the sleep quality (SQ) of intensive care unit (ICU) nurses. In a double-blind, randomized controlled trial, 54 ICU nurses were randomly assigned to the intervention group ( n = 27) that received 220 mg zinc sulfate capsules every 72 hours for 1 month and the control group ( n = 26) that received placebo. Sleep quality of ICU nurses was measured by calculating the total quality sleep score using the Pittsburgh Sleep Quality Index (PSQI). The serum zinc l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Furthermore, as a result of zinc supplementation, serum zinc levels in the intervention group increased significantly, which was consistent with most previous studies 29,30 . Karagozoglu et al study aimed to determine the effect of zinc supplementation on serum zinc concentrations in the elderly.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, as a result of zinc supplementation, serum zinc levels in the intervention group increased significantly, which was consistent with most previous studies 29,30 . Karagozoglu et al study aimed to determine the effect of zinc supplementation on serum zinc concentrations in the elderly.…”
Section: Discussionsupporting
confidence: 88%
“…The methods employed to measure sleep outcomes varied across studies. Seven studies used subjective measures (i.e., diaries/logbooks and sleep questionnaires) [31][32][33][34][35][36][37], while one study used PSG/EEG [38,39], and five studies used a combination of PSG/EEG or actigraphy, and subjective measures [39][40][41][42][43].…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…One study examining zinc supplementation in individuals with below-optimal zinc levels (≀ 79.9 ”g/dL) observed improvements in global sleep quality scores on the PSQI, subjective sleep quality, and sleep onset latency scores [32]. A separate study, which administered astaxanthin (a keto-carotenoid) in combination with zinc [43], observed a significant improvement in sleep onset latency, but no effects on total sleep time or sleep efficiency.…”
Section: Zincmentioning
confidence: 99%
“…This study showed that Zn has the ability to improve sleep after being ingested for several months. Baradari et al (2018) also found that zinc improved sleep quality and sleep latency in nurses; the dose used was 220 mg. However, ingestion of too much Zn may be problematic in AD patients since administration of Zn could possibly lead to enhanced AD pathology as discussed below.…”
Section: The Role Of Zinc In Sleepmentioning
confidence: 97%